Modelling the Dimensions of a Competitive Intelligence – Based Corporate Culture Using the Digital Memory BRAIN 7 - Blandine VANDERLINDEN (Revista de Management Comparat International)
In the context of a dynamic business environment, leading software companies are focusing their strategies on a market-driven approach, exploiting the opportunities provided by competitive intelligence mechanisms, in order to continuously monitor the competitive landscape. Being aware of the lack of cultural patterns aligned to competitive intelligence issues from software industry, we intend to further explain the design of specific dimensions related to a competitive intelligence (CI) based organizational cultural pattern, which is customized for software companies. Our paper highlights the creative task of conceiving several dimensions of analysis which characterize the cultural aspects from the organizational life of software companies; by interpreting the information resulted during the open discussions with IT experts from Belgium software industry and taking into consideration the evidence that every organization involved in software development has different goals and requirements for a CI based culture, we propose four dimensions of analysis: expert-coder versus utility developer, competing on talents versus competing on technology, creative impulses versus procedure compliance and shared CI data versus classified CI data. The ideas launched during the interviews were interconnected in a digital map provided by the software “The Brain7”. We identify areas for further research by crossing the most relevant dimensions of analysis and outline the opportunities for the integration of CI within the corporate culture.